Achieving an unprecedented hydrogen evolution rate by solvent-exfoliated CPP-based photocatalysts. Issue 12 (17th February 2020) - Cheng, Jing-Zhao; Liu, Li-Lin; Liao, Guangfu; Shen, Zhao-Qi; Tan, Zhi-Rong; Xing, Yu-Qin; Li, Xiao-Xiao; Yang, Kai; Chen, Long; Liu, Shi-Yong
Abstract : Solvent-exfoliated CPP-based photocatalysts have been innovatively used for photocatalytic hydrogen production with an unprecedented HER of up to 303.7 mmol h −1 g −1 . Abstract : How to prompt higher photocatalytic hydrogen production (PHP) efficiency from water to achieve practical applications still remains a big challenge with conjugated porous polymers (CPP)-based photocatalysts. Herein, we developed a simple and efficient cosolvent-assisted strategy to significantly improve the photocatalytic efficiency of CPP-based photocatalysts by introducing water-soluble aprotic bipolar co-solvents, including N, N -dimethylformamide (DMF), N, N -dimethylacetamide (DMAc), and N -methyl pyrrolidone (NMP). The PHP activity of the pyrene–bithiophene-based CPP (named CP- St ) using ascorbic acid (AA) as a sacrificial electron donor could be excellently accelerated in the presence of an aprotic bipolar NMP solvent. CP- St dispersed in an NMP/H2 O/AA mixed solution under visible-light ( λ > 420 nm) irradiation without the aid of a Pt cocatalyst achieved an unprecedented hydrogen evolution rate (HER) of 190.7 mmol h −1 g −1 . As a result, 6 mg CP- St amazingly produced 128.1 mL H2 (∼5.72 mmol) under visible-light irradiation for only 5 h. Excitingly, by introducing 0.5 wt% Pt cocatalyst into the NMP/H2 O/AA system, the HER of CP- St could be further boosted to 303.7 mmol h −1 g −1 (1.82 mmol h −1 /6 mg), which represents the highest photocatalytic HER ever reported. This outstanding photocatalytic performance is mainly ascribed to the enhanced dispersity, strong hydrogen-bond interactions, and exfoliation effect by the NMP solvent. This study provides us with some new design ideas and opportunities for effectively catering to the actual hydrogen production demand.